MONITORING THE USAGE OF MARINE FUEL OIL ABOARD PASSANGER SHIP BASED ON INTERNET OF THINGS - Sarman Sarman; Arief Marwanto; Suryani Alifah (Journal of Telematics and Informatics, 2020)
Measurement of the remaining MFO oil in the tank when the ship is sailing makes the crew become more troublesome because it must be reported within a certain period of time, for example every once an hour using a pendulum sensor. The measurement using this pendulum sensor the accuracy and precision of each becomes a deficiency of the value produced because the position of the ship is not taken into account. Another disadvantage of conventional methods is that fraud can occur if the tank capacity is full by manually falsifying measurement data, then MFO can be sold in the middle of the sea to fishermen or smuggled illegally to an outside country. To overcome these problems, the need for special monitoring for the availability of MFO oil in tanks by ship-owners needs to be carried out. In this case the accuracy, precision and the need for data that is always displayed and known by ship-owners is very important for the business management process of the company. For that, a precise, accurate and real-time fuel consumption monitoring tool is needed. As a comparison, manual measurement of appeal sensors was also carried out in order to get a more significant comparison value. There are 4 HC-SR04 ultrasonic sensors needed to get accuracy and precision on the position of the ship such as horizontal, tilted to the right, tilted to the left with a slope of 8 degrees and 16 degrees. The test results have shown that the four HC-SR04 sensors are able to read more accurate than the pendulum sensors in various ship positions. The reading result with HC-SR04 sensor has an error below 5% compared to an error in the pendulum sensor of 7.5%. Then, the mean error on the surface of the tank with the condition of a flat vessel of 2, 08%, on the position of the tilted vessel of 2.17% and the condition of the ship with a bumpy wave of 3.35%. The results of the measurement of the MFO volume in the tank sent through the internet to the monitoring station can be perfectly received so that it becomes accurate and real-time information for the observation of fuel consumption by the company management. Thus the prototype of monitoring the use of MFO fuel on passenger ships can be used to replace conventional measurement models which use pendulum sensors. Keywords: Arduino Uno, Ultrasonic Sensor, Potentiometer Pendulum Sensor, Esp 8266